Perceptions of Overuse Injury Among Swedish Ultramarathon and Marathon Runners: Cross-Sectional Study Based on the Illness Perception Questionnaire Revised (IPQ-R) - Wickström, William; Spreco, Armin; Bargoria, Victor; Elinder, Fredrik; Hansson, Per-Olof; Dahlström, Örjan; Timpka, Toomas (Frontiers in Psychology, 2019)
Background Psychological characteristics of long-distance runners with relevance for prevention of overuse injuries are not well understood. The aim of this study was to investigate perceptions of the nature and causes of overuse injury among ultramarathon and marathon runners with different exercise loads. Methods The study was based on a cross-sectional design. The Illness Perception Questionnaire Revised (IPQ-R) was used to investigate Swedish ultramarathon and marathon runners' perceptions of overuse injuries. Cluster analysis was employed for categorizing runners with regard to exercise load and sex. Factor analysis was thereafter used to group IPQ-R variables describing injury causes. Multiple logistic regression methods were finally applied to identify differences in injury perceptions between runners in the high and low load categories. Results Complete data sets were collected data from 165/443 (37.2%) runners. The symptoms most commonly assessed to be associated with overuse injury were pain (80% of the respondents), stiff muscles (54%), stiff joints (42%), and impaired physical ability (40%). The nature of overuse injury was perceived to be characterized by personal control, treatability, and that the general context of injury occurrence and management was comprehensible. The main injury causes highlighted were runner biomechanics, the runner's personality, and biomechanics associated with the running surface. Among men, runners with high exercise load considered personality to contribute to injury causation more than runners with lower loads (Odds ratio (OR) 2.10 (95% Confidence interval (95% CI) 1.38-3.19); P=0.001), while they downplayed the impact from running biomechanics (OR 0.56 (95% CI 0.37-0.85); P=0.006) and running mileage (OR 0.72 (95% CI 0.54-0.96); P=0.026). Among women, runners with higher exercise loads found it less likely that overload injuries can be controlled by medical interventions (OR 0.68 (95% CI 0.52-0.89); P=0.005). Conclusions Long-distance runners with a high exercise load were more likely than runners with lower loads to perceive that overuse injuries are associated with the runner’s personality and cannot be managed by medical interventions. The results indicate that awareness of the association between runner’s own decisions and tissue damage in overuse injury causation is underscored with rising running experience.